Role of social learning in labour producivity in Pakistan's manufacturing sector - Aslam, Wasim (2016)
This study is about the role and the process of social learning among the illiterate labour in gaining soft skill from their social environment, and how its influence their productivity. This research is conducted in Pakistan as this country experiences low productivity for decades and having more than 50% of illiterate labor. Labour’s education in Pakistan has been very low and this has influenced their productivity and vulnerability in industrial relation. The social learning process involving illiterate labour enable them to gain soft skills such as motivation, leadership, self-efficacy, and self-determination is very important to research, especially to measure their capacity and capability. This research is conducted in Nishat Textile Company as one of the manufacturing sectors which has high percentage of illiterate labour. Mix method is used to answer four research questions. To answer the first two research questions needs qualitative research. Then, to answer the second two research questions needs quantitative research method. The objective of using qualitative method is to understand the social learning process of how labour gaining soft skill from their manager, supervisor, and labour union leader. This method includes observation of the social learning process within the context of social relation of production in the company, interviewing all agencies involved in the social learning process in the company. The objective using quantitative research method is to examine the correlation of social learning and labour productivity. The quantitative research involved 300 respondents who are working in Nishat Textiles Company. This qualitative study found that the social relation of production in manufacturing sector not only construct the social structure of production but also has become the social environment where the process of social learning occurs. Labour’s are gaining soft skill from the agencies in the company social structure. This quantitative study found that social learning is positively influencing labor productivity. By controlling social learning effects in the model, Human capital was founded to be positively influencing labor productivity. By controlling human capital effects in the model, social learning was founded to be not significantly influencing labor productivity. Since the social learning is not significant in the second model, so human capital is found to be the mediator for the influencing of social learning on labor productivity. The implication of this study is offering a strategy to understand the potential of social learning within the social relation of production which function to improve the capacity and capability of the illiterate labours. Increasing their capacity and capability through social learning will increase labour productivity as well as to benefit them financially and reduce the employees’ vulnerability.